Hubungan Keharmonisan Keluarga dengan Perkembangan Moral Siswa Kelas IV dan V di MI Darul Falah Ngrangkok Klampisan Kandangan Kediri - Rif'an Fauzi (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2014)
Communities in Ngrangkok Klampisan Kandangan Kediri, low education, no awareness of education, being married young, there is no maturity in the household, the child eventually become victims. Question of how the family harmony, moral development of students and whether there are relationships with family harmony moral development of students grade IV and V MI Darul Falah Ngrangkok Klampisan Kandangan Kediri? The purpose knows the family harmony, moral development of students and there is relationship family harmony with moral development of students grade IV and V MI Darul Falah Ngrangkok Klampisan Kandangan Kediri. This research, field research to see the relationship of family harmony with moral development of students, sample student grade IV and V is 47 MI students of Darul Falah Ngrangkok Klampisan Kandangan Kediri, the analytical techniques coefficient product moment correlation of Karl Pearson. Conclusion there is relationship to the family harmony with moral development of students, because the harmony of the family support factor determining the moral development of students even though there are other factors influencing it. Results in MI Darul Falah Ngrangkok Klampisan Kandangan Kediri, the value of 0.99 r count> r table 0.334 (5%) and 0.99 count r> 0.430 (1%), very significant meaning accepted working hypothesis,